The Influence of Pseudo Auditor Rotation on Audit Quality: New Evidence - Rahmat Febrianto; Fitria Dini; Dela Audina; Yuskar Yuskar; Verni Juita (Australasian Accounting, Business and Finance Journal, 2017)
The objectives of this research are twofold, to test the audit quality of companies that change their auditors either voluntarily or mandatorily and to test the financial characteristics as a factor for an accounting firm to engage in pseudo mandatory rotation. Since 2002, Indonesia has had legislation mandating companies to rotate their auditor after six years of consecutive engagements (five years prior to 2008). However, auditors sometimes seem to find their own way to deceive the mandatory regulation by a tactic called “pseudo” mandatory rotation. Thus, we divide mandatory rotation into two categories, pure and pseudo mandatory rotation. The results of the data we collected since the Ministerial decree became effective in 2003 indicate companies that rotate their auditors mandatorily have higher audit quality than that of companies voluntarily rotating auditors. However, we cannot find evidence that pseudo and pure mandatory rotation have different audit qualities. The results also indicate that switching among bigger accounting firms have the highest audit quality rather than switching between smaller audit firms which have lower audit quality. Lastly, the motives of an accounting firm to engage in pseudo or pure mandatory rotation are related to the financial size of their clients. Future research must consider the limitation stated in this study.
Keywords: audit quality; auditor switching; discretionary accruals; pseudo and pure mandatory rotation; voluntary rotation; Indonesia